Factors influencing local control in patients undergoing breast conservation surgery for ductal carcinoma in situ. (February 2017) - Mathew, J.; Karia, R.; Morgan, D.A.L.; Lee, A.H.S.; Ellis, I.O.; Robertson, J.F.R.; Bello, A.M.
Abstract: Background: The aim of our study was to assess various predictors for local recurrence (LR) in patients undergoing breast conservation surgery (BCS) for ductal carcinoma in situ (DCIS). Materials and methods: An audit was performed of 582 consecutive patients with DCIS between Jan 1975 to June 2008. In patients undergoing BCS, local guidelines reported a margin of ≥10 mm during the above period. Guideline with regard to margin of excision changes soon after this period. We retrospectively analysed clinical and pathological risk factors for local recurrence in patients undergoing BCS. Statistical analysis was carried out using SPSS version 19, and a cox regression model for multivariate analysis of local recurrence was used. Results: Overall 239 women had BCS for DCIS during the above period. The actuarial 5-year recurrence rate was 9.6%. The overall LR rate was 17% (40/239. LR was more common in patients ≤50 years: (10/31 patients, 32%) compared to patients > 50 years (30/208, 14%, P = 0.02). Forty three per cent of patients (6/14) with <5 mm margin developed LR which was significantly higher compared to patients with 5–9 mm margin (12%, 3/25) and with ≥10 mm margin (14%, 27/188, P = 0.01). On multivariate analysis age ≤50 years, <5 mm pathological margin were independent prognostic factors for local recurrence. Conclusion: Our study shows that younger age (≤50 years) and a margin < 5 mm are poor prognostic factors for LR in patients undergoing breast conservation surgery for DCIS. Highlights: The study looks into predictors for local recurrence in patients undergoing BCS for DCIS. 239 women who had BCS for DCIS were retrospectively analysed for predictors for local recurrence. Young age (≤50 years) and margin <5 mm were poor prognostic factors for local recurrence.